2017
DOI: 10.1002/ccd.27204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates, and impact of coronary calcification on adverse events following PCI with newer‐generation DES: Findings from a large multiethnic registry

Abstract: Target lesion calcification remains independently associated with adverse outcomes in patients treated with newer generation DES and modern devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 24 publications
3
55
0
4
Order By: Relevance
“…A large multiethnic registry retrospectively assessed patients, who had undergone stent implantation between 2009 and 2013, according to coronary calcification 24 . A total of 994 (8.0%) of these patients were treated with second‐generation durable polymer DES for severely calcified lesions, and the 1‐year incidence of the composite clinical endpoint of death, myocardial infarction, or TVR (17.8%) was much higher than the 2‐year incidence of target vessel failure in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…A large multiethnic registry retrospectively assessed patients, who had undergone stent implantation between 2009 and 2013, according to coronary calcification 24 . A total of 994 (8.0%) of these patients were treated with second‐generation durable polymer DES for severely calcified lesions, and the 1‐year incidence of the composite clinical endpoint of death, myocardial infarction, or TVR (17.8%) was much higher than the 2‐year incidence of target vessel failure in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…The Synergy Between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score is the method utilized to evaluate coronary disease's complexity. The primary factors of high scores are the sites and severity of lesions [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Trials assessing the impact of calcium are often retrospective, include pooled subjects from multiple trials, combine moderate and severe calcium, or use investigator reported calcification . In contrast, the MACE‐Trial was intended to provide a standardized assessment of outcomes in subjects treated with standard‐of‐care PCI techniques stratified by lesion calcification.…”
Section: Discussionmentioning
confidence: 99%
“…One‐year MACE‐Trial outcomes were different from other contemporary studies that indicate that moderate calcium negatively impacts outcomes. Pooled data from ACUITY and HORIZONS‐AMI demonstrated that in addition to severe calcification, moderate calcification did have a significant impact on 1‐year MACE (19.9% and 15.3%, respectively) as compared to none/mild (12.9%); reported outcomes in Copeland‐Halperin et al (8.3% none/mild, 14.6% moderate, and 17.7% severe) resulted in a similar conclusion . Additionally, compared to Copeland‐Halperin et al, the MACE‐Trial reported lower rates of 1‐year MACE for none/mild and moderate, but outcomes for severely calcified subjects were considerably higher.…”
Section: Discussionmentioning
confidence: 99%